Cholinergic regulation of the rat adrenal zona glomerulosa - Jánossy, A; Orsó, E; Szalay, K S; Jurányi, Z; Beck, M; Vizi, E S; Vinson, G P (Journal of endocrinology, 1998)
Using histochemical and immunocytochemical methods, cholinergic nerve fibres were demonstrated in the rat adrenal cortex, primarily in the capsule and zona glomerulosa, and in the medulla. Some terminated among the glomerulosa cells or around blood vessels. Occasional fibres were also seen in the fasciculata, ending in islets of chromaffin tissue without ramifications on cortical cells. To clarify the role of cholinergic innervation, a microvolume perifusion system was used to study steroid production by the rat adrenal capsule-glomerulosa. Acetylcholine (ACh) itself had no reproducible effects; however, since variable amounts of endogenous ACh were present, the actions of antagonists were also studied. The M1 muscarinic receptor antagonist pirenzepine (10 and 100 microM) stimulated aldosterone secretion. This stimulation was abolished by co-incubation with carbachol, the M1 agonist McN A-343 and by atropine. We found that the action of pirenzepine was blocked by nifedipine (Ca2+ channel blocker), suggesting that pirenzepine (through release of endogenous ACh) provides an acute stimulus by enhancing Ca2+ inflow. Hemicholine, a choline uptake blocker, reduced the stimulatory effect of pirenzepine on steroid secretion, confirming that stimulation was of neural origin. Neither the non-selective muscarinic receptor antagonist atropine, the selective M1-M3 muscarinic receptor antagonist 4-DAMP, nor the selective M2 muscarinic receptor antagonist methoctramine influenced aldosterone output. Receptor-binding studies revealed the existence of M3 receptors in capsule-glomerulosa homogenates. We conclude that pirenzepine acts on presynaptic M1 autoreceptors to increase spontaneous ACh release from varicose axon terminals that lie in close proximity to the glomerulosa cells. In turn ACh may thus stimulate steroidogenesis acutely through M3 receptors. These results support the concept of a direct cholinergic influence on zona glomerulosa function in the rat.